2020
DOI: 10.1177/2210491720928472
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty: A single centre review at 10 years of follow-up

Abstract: Background: Total knee arthroplasty is a common procedure for treatment of various non-infective arthritis. This study reviewed total knee arthroplasty cases up to 10 years of follow-up for the survival rate, reasons of revision and associated perioperative risk factors for revision. Methods: All cases to total knee arthroplasty performed in a single centre in the years 2007 and 2008 were reviewed. A total of 227 cases of total knee arthroplasty were performed during the 2-year period, with 156 cases followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In another study from a center with similar demographics, a longer operative team in the initial arthroplasty is related to subsequent revision arthroplasty. 30 In a recent local study, Siu et al 31 stated that gram positive Staphylococcus was most common infective organism. Similarly in this study, infective organism identified were predominately gram positive cocci (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study from a center with similar demographics, a longer operative team in the initial arthroplasty is related to subsequent revision arthroplasty. 30 In a recent local study, Siu et al 31 stated that gram positive Staphylococcus was most common infective organism. Similarly in this study, infective organism identified were predominately gram positive cocci (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In another study from a center with similar demographics, a longer operative team in the initial arthroplasty is related to subsequent revision arthroplasty. 30…”
Section: Discussionmentioning
confidence: 99%
“…Failure most commonly occurs due to fatigue and adhesive wear, which are responsible for the generation of micro particulate debris that, in turn, cause osteolysis around the replacements, ultimately leading to loosening and failure of the TKR [7][8][9]. The survival rate of total knee replacements (TKR) has been reported to increase along with the development of advanced technologies and operative techniques [10][11][12].…”
Section: Introductionmentioning
confidence: 99%